Sensitivity, specificity, and tolerability of the BACTrack Skyn compared to other alcohol monitoring approaches among young adults in a field‐based setting. (14th May 2022) - Ash, Garrett I.; Gueorguieva, Ralitza; Barnett, Nancy P.; Wang, Wuyi; Robledo, David S.; DeMartini, Kelly S.; Pittman, Brian; Redeker, Nancy S.; O'Malley, Stephanie S.; Fucito, Lisa M.
Abstract: Background: There is a need for novel alcohol biosensors that are accurate, able to detect alcohol concentration close in time to consumption, and feasible and acceptable for many clinical and research applications. We evaluated the field accuracy and tolerability of novel (BACTrack Skyn ) and established (Alcohol Monitoring Systems SCRAM CAM ) alcohol biosensors. Methods: The sensor and diary data were collected in a larger study of a biofeedback intervention and compared observationally in the present sub‐study. Participants (high‐risk drinkers, 40% female; median age 21) wore both Skyn and SCRAM CAM sensors for 1–6 days and were instructed to drink as usual. Data from the first cohort of participants ( N = 27; 101 person‐days) were used to find threshold values of transdermal alcohol that classified each day as meeting or not meeting defined levels of drinking (heavy, above‐moderate, any). These values were used to develop scoring metrics that were subsequently tested using the second cohort ( N = 20; 57 person‐days). Data from both biosensors were compared to mobile diary self‐report to evaluate sensitivity and specificity in relation to a priori standards established in the literature. Results: Skyn classification rules for Cohort #1 within 3 months of device shipment showed excellent sensitivity for heavy drinking (94%) and exceeded expectations for above‐moderate and any drinking (78% and 69%, respectively), while specificity met expectations (91%). However, classification worsened when Cohort #1 devices ≥3 months from shipment were tested (area under curve for receiver operator characteristic 0.87 vs. 0.79) and the derived classification threshold when applied to Cohort #2 was inadequately specific (70%). Skyn tolerability metrics were excellent and exceeded the SCRAM CAM ( p ≤ 0.001). Conclusions: Skyn tolerability was favorable and accuracy rules were internally derivable but did not yield useful scoring metrics going forward across device lots and months of usage. Abstract : The BACTrack Skyn is a new wearable sensor with potential to detect alcohol accurately and promptly with minimal user burden. Worn under conditions of daily living by 27 high‐risk drinkers, the Skyn was highly tolerable, showed excellent sensitivity for heavy drinking (94%), exceeded expectations for above‐moderate and any drinking (78%/69%), while specificity met expectations (91%). Unfortunately, the drinking detection rules were not robust across timeframes >3 months among different device lots and individuals. Further analytical and hardware developments are encouraged.